Genesis Rabbah - An Opportunity for Interfaith Dialogue: Augustine, Milton, and the Rabbis of Genesis Rabbah in Discourse - Cronin, Sonya Shetty (Journal of ecumenical studies, 2018)
When reading biblical texts, there are often what can be termed "gaps" in the narrative, aspects of the story that need more detail or simply do not make obvious sense, leading to more questions. This leads to the need for interpretation. While the term "midrash" refers to a particularly "Jewish" mode of interpretation of the biblical narrative, the method of "the filling in of the gaps" is something done by religious interpreters of all traditions. This essay puts the rabbis of Genesis Rabbah (midrash) in conversation with fourth-century theologian Augustine and fifteenth-century author John Milton regarding their interpretation of Genesis 3, demonstrating how this kind of interaction can foster interfaith dialogue in the modern classroom.